Analisis Interpretasi Tekstual dan Kontekstual tentang Pendidikan Karakter dalam al-Qur’an - Arcanita, Rafia; Febriyarni, Busra (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Abstract. Islam is a religionrahmatan lil alamin, namely a religion that brings goodness to anyone around it. Because Islam regulates all the behavior of its people contained in the Al-Qur'an and Hadith. There are many character education values contained in the Qur'an, one of which is found in the Al-Qur'an letter Al-Isra’ verse 36 and the Al-Qur'an letter Az-Zumar verse 39. In the Al-Qur'an letter Al-Isra’ verse 36, character education which is very clearly taught to Muslims is to instill the value of love for Allah and the creatures around him, namely to teach Muslims to always fear Allah and keep their sight, hearing and carefully so as not to hurt the feelings of those around him. Then instill the value of responsibility and trustworthiness. Furthermore, in the Al-Qur'an letter Az-Zumar verse 39, character education that is very clearly taught to Muslims is an attitude of love for Allah by maintaining piety to Allah, then an attitude of responsibility realizing that those who are responsible for human beings are humans themselves , as well as the character value of wanting to work hard, namely by always trying to work with all the abilities possessed by the human himself and leaving the results to Allah SWT.